2011
DOI: 10.1007/s11051-011-0237-y
|View full text |Cite
|
Sign up to set email alerts
|

Designing oversight for nanomedicine research in human subjects: systematic analysis of exceptional oversight for emerging technologies

Abstract: The basic procedures and rules for oversight of U.S. human subjects research have been in place since 1981. Certain types of human subjects research, however, have provoked creation of additional mechanisms and rules beyond the Department of Health & Human Services (DHHS) Common Rule and Food and Drug Administration (FDA) equivalent. Now another emerging domain of human subjects research—nanomedicine—is prompting calls for extra oversight. However, in 30 years of overseeing research on human beings, we have ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
0
9
0
2
Order By: Relevance
“…Clinical trials are expensive and their costs will likely increase in the future [88]. The oversight for nanomedicine may increase since it is an emerging technology with potential risks to be determined [89].…”
Section: Nanomedicine Business Model Selectionmentioning
confidence: 99%
“…Clinical trials are expensive and their costs will likely increase in the future [88]. The oversight for nanomedicine may increase since it is an emerging technology with potential risks to be determined [89].…”
Section: Nanomedicine Business Model Selectionmentioning
confidence: 99%
“…However, governmental regulations are hindered by a lack of toxicology data for nanocarriers (Fernandes et al 2010 ;Farrell et al 2011 ). In addition, Wolf and Jones ( 2011 ) have recommended extra oversight for clinical research due to the uncertain but possibly signifi cant risks of new science and technology associated with nanomedicine (including drug nanocarriers).…”
Section: Criteria For Nanocarriers To Move Into Clinical Practicementioning
confidence: 99%
“…Providing preclinical proof that the investigational product is safe is one consideration, while regulatory aspects make up another. Wolf and Jones ( 2011 ) have recently reviewed whether or not it is necessary to have extra oversight, i.e., additional approval processes beyond the current institutional review boards (IRB) for emerging technologies such as nanocarriers. They claim that there is a heightened uncertainty regarding the risks in fast-evolving science, yielding complex and increasingly active materials.…”
Section: Clinical Researchmentioning
confidence: 99%
“…Heightened uncertainty regarding risks, fast-evolving science yielding complex and increasingly active materials, likelihood of research on vulnerable participants including cancer patients, and potential risks to others beyond the research participant are identified as relevant confluent factors in support of the need for an exceptional oversight beyond the existing Common Rules 6 supervised by either local or federal institutions such as the US Department of Health and Human Services, the Federal Drug Administration (FDA), notably its Centres in charge of overseeing drug, biologics, and device approval, the National Institutes of Health or the National Cancer Institute (Wolf and Jones, 2011). Concern regarding potential risks does not involve only the volunteers and candidates recruited to participate to clinical trials, but also workers employed in the manufacturing industries, as well as, during the fundamental research stage, scientists conducting experiments in public or private laboratories.…”
Section: An Overview Of Nanomedicinementioning
confidence: 99%
“…Thus, beyond the individual approach, the core of this work also concentrates on workers' safety, and to a certain extent, exposure of close contacts and community effects. Indeed, since laboratory practices, waste, as well as human subject excretion of nanomaterials can raise environmental concern, analysis of environmental effects should also be examined (Wolf and Jones, 2011).…”
Section: General Framework Of the Case Studymentioning
confidence: 99%